2021
DOI: 10.1042/bsr20211143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anticancer effects of Juniperus communis extract on hepatocellular carcinoma cells in vitro and in vivo

Abstract: Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer and accounts for the fourth leading cause of all cancer deaths. Scientific evidence has found that plant extracts seem to be a reliable choice due to their multitarget effects against HCC. Juniperus communis has been used for centuries in traditional medicine and has reported its anticancer properties. As a result, the purpose of the study was to investigate the anticancer effect and mechanism of JCo extract on HCC in vitro and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…These data are in agreement with in vivo results [ 73 ]. Furthermore, this plant also showed potential to inhibit HepG2, Mahlavu, and J5 human hepatocellular carcinoma cell growth, in a dose- and time-dependent manner, revealing IC 50 values of 43.9 µg/mL for HepG2 cells, 59.4 µg/mL for Mahlavu cells, and 53.2 µg/mL for J5 cells after 72 h of treatment [ 132 ].…”
Section: Biological Potential Of Juniperus Communis ...mentioning
confidence: 99%
See 2 more Smart Citations
“…These data are in agreement with in vivo results [ 73 ]. Furthermore, this plant also showed potential to inhibit HepG2, Mahlavu, and J5 human hepatocellular carcinoma cell growth, in a dose- and time-dependent manner, revealing IC 50 values of 43.9 µg/mL for HepG2 cells, 59.4 µg/mL for Mahlavu cells, and 53.2 µg/mL for J5 cells after 72 h of treatment [ 132 ].…”
Section: Biological Potential Of Juniperus Communis ...mentioning
confidence: 99%
“…It was also verified that J. communis treatment resulted in cell-cycle arrest at the G0/G1 phase; lower concentrations of B-cell lymphoma-2 (Bcl-2), procaspases 8 and 9; and higher levels of Bcl-2-associated X protein, apoptosis-inducing factor, cell-surface death receptor Fas, and Fas ligand [ 73 ]. On the other hand, the administration of J. communis essential oils (200 mg/kg) in BALB/c nude mice injected with HepG2 cancer cells showed the capacity to reduce tumor growth and extend the lifespan with no or low systemic and pathological toxicity [ 132 ]. Similar information was reported by Lai and colleagues [ 133 ] and Tsai and collaborators [ 135 ] regarding the antitumor effects of this plant against human colorectal adenocarcinoma and glioblastoma.…”
Section: Biological Potential Of Juniperus Communis ...mentioning
confidence: 99%
See 1 more Smart Citation
“…JCo extract contains α‐pinene, β‐pinene, apigenin, sabinene, β‐sitosterol, campesterol, limonene, and cupressuflavone, among other compounds (Bais et al, 2014; Li et al, 2021). JCo extract has been experimentally demonstrated to have antioxidant, antibacterial, antiviral, antifungal, anticancer, and anti‐inflammatory effects (Huang et al, 2021; Moein et al, 2010; Raina et al, 2019), thus making it a potential therapeutic agent. However, few studies have investigated the anti‐inflammatory and antioxidant mechanism and pathophysiology of JCo extract in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…(Wambua Mukavi et al, 2020 ), Diospyros kaki leaves (Ko et al, 2020 ), Licorice (Wang, Luo, et al, 2019 ), Phoenix dactylifera L. (Khan et al, 2017 ), germ and bran of red rice (Upanan et al, 2019 ), Coptis chinensis (Kim et al, 2021 ), and Juniperus communis Linn. (Huang et al, 2021 ), have been found to induce the apoptotic death of HepG2 cells via the exogenous, mitochondria‐mediated endogenous pathway, MAPK signaling pathway, and ER signaling pathway. Thus, these extracts have the potential for being developed into drugs that specifically target HCC.…”
Section: Introductionmentioning
confidence: 99%